Effect of sagittal plane deformity of the lumbar spine on epidural fibrosis formation after laminectomy - An experimental study in the rat - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2004)
Study Design. An animal model of postlaminectomy lumbar column sagittal plane deformity was designed in rats. Objectives. To analyze the effect of lumbar column deformity (lordosis and kyphosis) on postlaminectomy epidural fibrosis formation. Summary of Background Data. Incidence of peridural fibrosis formation after lumbar spinal surgery is considerably high. Instability and sagittal plane deformity of the lumbar spine has been implicated (not proven) as the factors for the development of epidural fibrosis. The effect of traction (kyphosis) or relaxation (lordosis) of the lumbar spine on epidural fibrosis formation is not known. Methods. L4 laminectomies were performed in 30 rats. Three equal groups were formed. In the control group (group I), only laminectomy was performed. In other groups after laminectomy, lumbar lordosis (group II) and kyphosis (group III) was maintained with steel implants. The scar formation was evaluated both histologically and histomorphometrically on the 12th postoperative week. Results. Kyphosis developed in group I. The mean amount of peridural scar tissue was significantly more evident in groups I and III than the lordosis group. The extent of adherence to the dura mater and the nerve roots was most apparent in group III. Conclusions. Kyphosis and consequent traction of the lumbar spine is one of the causes for increased epidural fibrosis formation after laminectomy. On the contrary, establishment of lordosis and relaxation of the lumbar spine decreased the scar tissue formation in rats.
Keywords: laminectomy; kyphosis; lordosis; epidural fibrosis; SCAR FORMATION; PERIDURAL FIBROSIS; PREVENTION; ADHESIONS; MEMBRANE; ARACHNOIDITIS; PROPHYLAXIS; OSTEOTOMY; SURGERY; RABBITS